Holocene changes in monsoon precipitation in the Andes of NE Peru based on δ18O speleothem records. (15th August 2016) - Bustamante, M.G.; Cruz, F.W.; Vuille, M.; Apaéstegui, J.; Strikis, N.; Panizo, G.; Novello, F.V.; Deininger, M.; Sifeddine, A.; Cheng, H.; Moquet, J.S.; Guyot, J.L.; et al.
Abstract: Two well-dated δ 18 O-speleothem records from Shatuca cave, situated on the northeastern flank of the Peruvian Andes (1960 m asl) were used to reconstruct high-resolution changes in precipitation during the Holocene in the South American Summer Monsoon region (SASM). The records show that precipitation increased gradually throughout the Holocene in parallel with the austral summer insolation trend modulated by the precession cycle. Additionally the Shatuca speleothem record shows several hydroclimatic changes on both longer- and shorter-term time scales, some of which have not been described in previous paleoclimatic reconstructions from the Andean region. Such climate episodes, marked by negative excursions in the Shatuca δ 18 O record were logged at 9.7–9.5, 9.2, 8.4, 8.1, 5.0, 4.1, 3.5, 3.0, 2.5, 2.1 and 1.5 ka b2k, and related to abrupt multi-decadal events in the SASM. Some of these events were likely associated with changes in sea surface temperatures (SST) during Bond events in the North Atlantic region. On longer time scales, the low δ 18 O values reported between 5.1-5.0, 3.5–3.0 and 1.5 ka b2k were contemporaneous with periods of increased sediment influx at Lake Pallcacocha in the Andes of Ecuador, suggesting that the late Holocene intensification of the monsoon recorded at Shatuca site may also have affected high altitudes of the equatorial Andes further north. Numerous episodes of low SASM intensity (dry events) were recorded by the Shatuca record during the Holocene, in particular at 10.2, 9.8, 9.3, 6.5, 5.1, 4.9, 2.5 and 2.3 ka b2k, some of them were synchronous with dry periods in previous Andean records. Highlights: Shatuca time series, recorded abrupt SASM events that seem to have a regional signal among South American paleorecords during the Holocene period. Some of these events were apparently related to the Bond events. The high resolution obtained for the early Holocene, allows observing abrupt monsoon changes not recorded by previous paleorecords. The high resolution of Shatuca record around 5 ka b2k, suggests that this was a period of extreme SASM variability. The Pallcacocha lake record seems to have recorded an increase of monsoon intensity, especially during the Bond events of the late Holocene.